2013
DOI: 10.4236/jct.2013.47137
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor: A Target for Breast Cancer Therapy

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that regulates a battery of genes in response to exposure to a broad class of environmental poly aromatic hydrocarbons (PAH). AhR is historically characterized for its role in mediating the toxicity and adaptive responses to these chemicals, however mounting evidence has established a role for it in ligand-independent physiological processes and pathological conditions, including cancer. The AhR is overexpressed and constitutively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 73 publications
(72 reference statements)
1
34
0
Order By: Relevance
“…In addition, a highly significant correlation between the AhR expression and invasive breast carcinoma was reported [41]. Recent studies have demonstrated that activation of AhR dramatically increased CSCs development and characteristics [21, 42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a highly significant correlation between the AhR expression and invasive breast carcinoma was reported [41]. Recent studies have demonstrated that activation of AhR dramatically increased CSCs development and characteristics [21, 42].…”
Section: Discussionmentioning
confidence: 99%
“…The AhR has been previously described in the initiation and progression of breast cancer (Nebert et al, 2004;Schlezinger et al, 2006;Vinothini and Nagini, 2010;Powell et al, 2013;Go et al, 2015). The metabolism of environmental toxins by the AhR leads credence to the proposal that the initial insult that caused the breast cancer was a fat-soluble xenobiotic element that was metabolized to a DNA-damaging compound.…”
Section: Discussionmentioning
confidence: 86%
“…A recent reduction in mortality rates, in the face of increased diagnoses, has been attributed to advances in early identification and treatment . Despite this reduction in mortality, the treatment of many types of breast cancer is complex and difficult . Ongoing improvements in the long‐term treatment and survival of women with breast cancer is further complicated by disease relapse and drug resistance …”
Section: Breast Cancer Backgroundmentioning
confidence: 99%
“…The aryl hydrocarbon receptor (AhR) is a member of the basic helix‐loop‐helix/Per‐ARNT‐SIM (bHLH/PAS) transcription factor family, and it has been previously suggested that it is a possible druggable target . It is ligand activated by a variety of synthetic and natural compounds .…”
Section: Aryl Hydrocarbon Receptormentioning
confidence: 99%